The Changes in Microbiotic Composition of Different Intestinal Tracts and the Effects of Supplemented Lactobacillus During the Formation of Goose Fatty Liver - Wen, Kang; Liu, Long; Zhao, Minmeng; Geng, Tuoyu; Gong, Daoqing (Frontiers in Microbiology, 2022)
Intestinal bacteria play an important role in the formation of fatty liver in animals by participating in the digestion and degradation of nutrients, producing various metabolites, and altering the barrier effect of the intestine. However, changes in the gut microbiota during the formation of goose fatty liver are unclear. In this study, 80 healthy Landes geese with similar body weights at 70 days of age were randomly divided into two groups: the control group (n=48; fed ad libitum) and the overfeeding group (n=32; overfed). The intestinal contents were collected at 0, 12, and 24 days of overfeeding. The 16S rRNA and metagenomic sequencing analyses showed that the dominant phylum, including Firmicutes, Proteobacteria, Bacteroidetes and Actinobacteria; at the genus level, Phyllobacterium, Bacteroides, Helicobacter, Lactobacillus, Enterococcus and Romboutsia were the dominant genera in the goose intestine, and most of them were probiotics; in the control state, the relative abundance of Firmicutes in the jejunum and ileum gradually decreased with time, while that of Proteobacteria increased, whereas in the overfeeding state, the relative abundance of Firmicutes in the jejunum and ileum decreased and then increased with time, while that of Proteobacteria showed an opposite trend. In addition, supplementing Lactobacillus to the diet reduced body weight and fatty liver weight in overfed geese, but increased the weight of abdominal fat, suggesting that Lactobacillus supplementation might affect the transport of nascent fat from the liver to abdominal fat. In conclusion, the species of intestinal-dominant bacteria in the geese are relatively stable, but their relative abundance and function are affected by a number of factors. Overfeeding promotes the metabolism of nutrients in the jejunum and ileum and increases bacterial adaptability to environmental changes by enhancing their environmental and genetic information processing ability. These findings suggest that the effect of overfeeding on the composition of intestinal microbiota may indirectly influence the formation of goose fatty liver through the gut/liver axis.